Activation as the quality index of medical care provided to patients suffering from nervous system diseases - Siwińska, Violetta; Iłżecka, Joanna; Iwanowicz-Palus, Grażyna (Polish Journal of Public Health, 2010)
Active people fall for various types of diseases very rarely. Obesity, atheromatosis, diabetes, coronary heart disease, faulty posture and many other diseases are the consequence of sedentary life style. Each person should endeavor to maintain the highest level of activity, not only in its physical, but also mental, social and spiritual sense thus enabling proper functioning in the surrounding environment. Diseases and disabilities do not eliminate the ability to act and to function in society, however these ailments frequently limit and hamper these spheres f life.In general, a person afflicted with a chronic disease with neurological background requires help and support. It is most common that these diseases in a later phase lead to decrepitude, loneliness and impediments in everyday life. Frequently, they become a problem and impair self-sufficient existence in normal environment leading to decrease in activity on various levels of patient’s life.On the basis of literature review and performed tests in the group of patients with nervous system diseases, it was discussed how the quality of care taken by a long-term institution influences the patients’ level of activity.On the basis of the conducted tests the following questions were raised: what level of activity do the patients suffering from neurological diseases obtain in their opinion; does the quality of taken care influence the level of patient’s activity; do the patient’s needs in living, social, economic and subjectivity spheres have impact on the quality of the care taken.